Preface - Bigham, Jeffrey; Parkes, David (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
This conference is an opportunity to build on the success of the First AAAI Human Computation and Crowd- sourcing conference, and to promote the best scholarship in this vibrant and fast emerging, multidisciplinary area. The conference also comes on the heels of four HCOMP workshops, including two workshops hosted at the annual AAAI conference.